If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5(a+4)=4(a+5)-4
We move all terms to the left:
5(a+4)-(4(a+5)-4)=0
We multiply parentheses
5a-(4(a+5)-4)+20=0
We calculate terms in parentheses: -(4(a+5)-4), so:We get rid of parentheses
4(a+5)-4
We multiply parentheses
4a+20-4
We add all the numbers together, and all the variables
4a+16
Back to the equation:
-(4a+16)
5a-4a-16+20=0
We add all the numbers together, and all the variables
a+4=0
We move all terms containing a to the left, all other terms to the right
a=-4
| 4-8x+20=60-|5+2x| | | -1/2(6x-10)-6=-6x+1-15 | | 7(-2x+3)=-21 | | 4=8+x/4 | | 18x-4=3x+78 | | 36x+24=12x+12(2+2x | | -1+15x=2+10x | | 148=(7x+15) | | 8x+16=12-60 | | -2+12+10x=4(2x+3) | | m−17/2=1 | | 2(x+3)=(-2x+4) | | -7+7a=4a+5 | | 13-5x=92 | | 8(1+5x+5-5x=13 | | 4x-18x=-36 | | 4(x+20)=3x+84−x4(x+20)=3x+84−x | | -10+3z=3z | | 3=3u-9 | | 2r-(-6.81)=19.27 | | 62=8+9h | | -4(-2x-6)=-8 | | 3x-9=1x-11 | | -2+9x=2+10x | | 15-5x-25=3x+6-6x-1 | | -6+9x=2+10x | | p-6=-5= | | -6+9x=2+6x | | 15=c/3+13 | | 4(1-2b)+7b-10=b | | 2(2a+3)-4(3a-6)=15 | | -9x+18=-3(x-4) |